An Alternative Estimator for Estimating the Finite Population Mean Using Auxiliary Information in Sample Surveys. (29th May 2012) - Solanki, Ramkrishna S.; Singh, Housila P.; Rathour, Anjana
Abstract : This paper suggests a class of estimators for estimating the finite population mean Y ¯ of the study variable y using known population mean X ¯ of the auxiliary variable x . Asymptotic expressions of bias and variance of the suggested class of estimators have been obtained. Asymptotic optimum estimator (AOE) in the class is identified along with its variance formula. It has been shown that the proposed class of estimators is more efficient than usual unbiased, usual ratio, usual product, Bahl and Tuteja (1991), and Kadilar and Cingi (2003) estimators under some realistic conditions. An empirical study is carried out to judge the merits of suggested estimator over other competitors practically.